The Influence of Good Corporate Governance and Corporate Social Responsibility on Tax Avoidance with Political Connections as a Moderating Variable - Indrawan, Ade Surya; Werastuti, Desak Nyoman Sri; Adiputra, I Made Pradana (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to examine the relationship between GCG and CSR on tax avoidance, with political connections as a moderating variable. The study employs a quantitative approach using Moderated Regression Analysis. The data were obtained from annual reports of companies selected through purposive sampling, resulting in a total of 96 observations from 16 companies over a six-year period. The findings indicate that GCG has a negative and significant effect on tax avoidance suggesting that the better the corporate governance practices the lower the likelihood of companies engaging in tax avoidance. Conversely, CSR is not proven to affect tax avoidance indicating that corporate social activities have not yet played a role in enhancing tax compliance. In addition, political connections are not able to moderate the relationship between GCG or CSR and tax avoidance, implying that closeness to political actors does not influence the effectiveness of governance practices or CSR initiatives in reducing opportunistic tax-related behaviors.